KEBERHASILAN STEK PUCUK TANAMAN GYRINOPS VERSTEEGII MELALUI PEMILIHAN MEDIA AKAR DAN ZAT PENGATUR TUMBUH (SUCCESS LEVEL OF THE SHOOT CUTTING ON GYRINOPS VERSTEEGII BY CHOOSING THE ROOTING MEDIA AND HORMONAL APPLICATION) - ali setyayudi (Journal Penelitian Kehutanan FALOAK, 2018)
The success of the shoot cutting can be influenced by the rooting media and rooting hormone application. This research aim to determine increasing of the success percentage of shoot cutting that influenced the rooting media and hormone. The trial was made by two design, they are the rooting hormone test and the rooting media test.  Six media used on the RCBD design, they are soils, soil+compost (3:1), cocopeat+sand (1:1), cocopeat+sand+ compost (1:1:2), soil+cocopeat+sand (2:1:1), dan soil+cocopeat+sand+compost (5:3:3:4). On the rooting hormone test use the two kind of hormone they are IBA and NAA with the concentration on 100ppm, 200ppm, 300ppm and the 0ppm for control unit. The result show that the soil and the IBA on 200ppm have the highest success percentage of rooting.Keywords : rooting media, gaharu, cutting